Impact of the COVID-19 Pandemic on Urological Care Delivery in the United States. Issue 6 (2nd December 2021) - Lee, Daniel J.; Shelton, Jeremy B.; Brendel, Paul; Doraiswami, Rahul; Makarov, Danil; Meeks, William; Fang, Raymond; Roe, Matthew T.; Cooperberg, Matthew R.
Abstract : Abstract : Purpose: We examined changes in urological care delivery due to COVID-19 in the U.S. based on patient, practice, and local/regional demographic and pandemic response features. Materials and Methods: We analyzed real-world data from the American Urological Association Quality (AQUA) Registry collected from electronic health record systems. Data represented 157 outpatient urological practices and 3, 165 providers across 48 U.S. states and territories, including 3, 297, 721 unique patients, 12, 488, 831 total outpatient visits and 2, 194, 456 procedures. The primary outcome measure was the number of outpatient visits and procedures performed (inpatient or outpatient) per practice per week, measured from January 2019 to February 2021. Results: We found large (>50%) declines in outpatient visits from March 2020 to April 2020 across patient demographic groups and states, regardless of timing of state stay-at-home orders. Nonurgent outpatient visits decreased more across various nonurgent procedures (49%–59%) than for procedures performed for potentially urgent diagnoses (38%–52%); surgical procedures for nonurgent conditions also decreased more (43%–79%) than those for potentially urgent conditions (43%–53%). African American patients had similar decreases in outpatient visits compared with Asians and Caucasians, but also slower recoveries back to baseline. Medicare-insured patients had the steepest declines (55%), while those on Medicaid and government insurance had the lowest percentage of recovery to baseline (73% and 69%, respectively). Conclusions: This study provides real-world evidence on the decline in urological care across demographic groups and practice settings, and demonstrates a differential impact on the utilization of urological health services by demographics and procedure type.